Simultaneous Regional Election Polemics in the Middle of the Covid-19 Pandemic - Adib Althof Rusydi; Achmad Sulchan (Jurnal Daulat Hukum, 2020)
The purpose of this study is to determine the impact of the simultaneous regional elections in the midst of the Covid-19 pandemic and efforts or solutions to minimize the impact that will occur. The research method uses a normative juridical approach. Then analyzed qualitatively with descriptive analytical method. The conclusion of this study is that in order to maintain the health of democracy, legality and legitimacy of elected regional heads and to protect public health in the implementation of the 2020 Regional Elections in the middle of the Covid-19 Pandemic, it is necessary to anticipate the possible risks posed by all stakeholders. Election organizers must be able to convince the public that the 2020 simultaneous regional elections are safe from potential exposure to the Covid-19 virus. Furthermore, the existence of legal sanctions for violators of health protocols and election administrators are required to maintain their independence, balance, assertiveness, and responsiveness in efforts to mitigate the electoral crisis amid the Covid-19 pandemic.